Tinjauan Hukum Pidana Internasional Atas Tindakan Eksploitasi Sumber Daya Perikanan Di Wilayah Laut ZEE Indonesia Oleh Kapal Asing - Sevti Prana Ningrum; Rizkita Brahmana; Siti Khodijah; Herly Antoni (Universitas Sang Bumi Ruwa Jurai, 2023)
The Exclusive Economic Zone (EEZ) is a new legal system regulated in the 1982 maritime law agreement between countries. Therefore, the abundant marine fisheries resources in Indonesia's EEZ allow for actions that are detrimental to being an archipelagic country due to violations committed by foreign countries that violate state sovereignty. Therefore, the Indonesian government has established legal rules regarding the use of fisheries resources and maritime boundaries in Law Number 17 of 1985 from the ratification of UNCLOS 82, and in its implementation these legal rules must not deviate from the Indonesian Constitution. Apart from vigilance, of course this is a a warning to the country in maintaining its sovereignty so that it is protected from intervention by foreign countries who secretly steal data on the country's territory and look for gaps in defense weaknesses through maritime boundaries. Therefore, all regulations regarding the territorial boundaries of the Exclusive Economic Zone (EEZ) have been summarized in UNCLOS 82. This article aims to explore aspects related to the protection of water resources in the EEZ and the provisions of international and transnational criminal law that anticipate the protection of water resources in the EEZ. This research utilizes normative methods that are descriptive in nature and tend to utilize data analysis.